Recent progress in porphyrin-based materials for organic solar cells. Issue 35 (24th August 2018) - Mahmood, Asif; Hu, Jian-Yong; Xiao, Bo; Tang, Ailing; Wang, Xiaochen; Zhou, Erjun
Abstract : This article is written to provide an up-to-date review of porphyrin-based materials used in organic solar cells (OSCs). Abstract : This article is written to provide an up-to-date review of porphyrin-based materials used in organic solar cells (OSCs). During the past two decades, OSCs have been the subject of extensive research and significant efforts have been devoted to developing low-cost OSCs, and they are not far from commercialization. Porphyrin and its analogues have been successfully applied to different optoelectronic devices, especially attaining remarkable fame when applied in dye sensitized solar cells. Despite the initial failures of their application in OSCs, porphyrins still attract much attention because of their structural versatility and recently realized significant improvement. In this review, we focus on summarizing the recent progress in porphyrin-based photovoltaic materials, including polymers, dyads, triads, small-molecules, and so on. We hope this paper could provide an in-depth study on the structure–property–performance relationship and provide a guideline for the further development of porphyrin-based and even other photovoltaic materials.